SKENARIO ALTERNATIF KEBIJAKAN PENINGKATAN ANGGARAN OPERASIONAL KELURAHAN - Dwinugraha, Akbar Pandu; Agustine, Adhinda Dewi (JPAP: Jurnal Penelitian Administrasi Publik, 2021)
It cannot be denied that the implementation of public services in the kelurahan should be supported by optimal operational funding according to the needs of the kelurahan. Unfortunately, the operational budgets that exist in each kelurahan are not currently based on a standard cost analysis that is able to accommodate the need to provide the community with a minimum service standard. This research uses descriptive qualitative research. Conducted in the City of Probolinggo, while the selection of research locations is determined based on the cluster of sub-districts in the City of Probolinggo by determining one sub-district to one village. The result of the research states that the method used in determining the amount of financing to each sub-district is top-down. The alternative policy scenario offered is to use a top down and bottom up combination model in calculating the distribution of operational funds to each sub-district. The percentage of calculating operational financing on average can be increased to 70%, while the proportion of proportional cost calculation for kelurahan can be reduced to 30% provided that adding the existing factors in the bottom up model is used as a calculation factor adding to the six pre-existing factors